2016
DOI: 10.1016/j.jclepro.2015.08.086
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and physical properties of regenerated cellulose fibres from cotton waste garments

Abstract: The aim of this research was to investigate the recycling of cotton waste garments by fibre regeneration. Easy care finished cotton fabrics and indigo dyed waste denim garments were successfully purified, dissolved in a suitable solvent and spun into fibres. The physical properties of the resultant fibres were compared with standard lyocell fibres spun from wood pulp and the fibres regenerated from the cotton waste garments exhibited improved mechanical and molecular properties relative to the typical fibres r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 28 publications
5
64
1
Order By: Relevance
“…The alkaline bleaching step on its own was not effective in dissolving the DMDHEU-treated wrinkle-free cotton in CED, but after the removal of DMDHEU and reactive dyes with the sequential acid step, the pulps were soluble in CED. The low solubility in CED of wrinkle-free DMDHEU-treated cotton fabrics confirms previous findings of Haule et al [13] that a combined alkaline/acid sequence effectively hydrolyses the DMDHEU wrinkle-free finish. Interestingly, the present study also found that the reactive dyes needed to be removed from the cotton fabric in an alkaline/acid bleaching sequence to obtain the limiting viscosity number of the pulp and hence a material suitable for the viscose process.…”
Section: Bleaching Of Cotton Fabricssupporting
confidence: 89%
See 1 more Smart Citation
“…The alkaline bleaching step on its own was not effective in dissolving the DMDHEU-treated wrinkle-free cotton in CED, but after the removal of DMDHEU and reactive dyes with the sequential acid step, the pulps were soluble in CED. The low solubility in CED of wrinkle-free DMDHEU-treated cotton fabrics confirms previous findings of Haule et al [13] that a combined alkaline/acid sequence effectively hydrolyses the DMDHEU wrinkle-free finish. Interestingly, the present study also found that the reactive dyes needed to be removed from the cotton fabric in an alkaline/acid bleaching sequence to obtain the limiting viscosity number of the pulp and hence a material suitable for the viscose process.…”
Section: Bleaching Of Cotton Fabricssupporting
confidence: 89%
“…Furthermore, Haule et al [6] demonstrated that the easy-care DMDHEU crosslinker could successfully be removed from cotton cellulose by applying 23 wt% sodium hydroxide solution at 100 °C, followed by concentrated sulphuric acid and then rinsing in 23 wt% sodium hydroxide solution at 100 °C. A later publication reported that cotton pulp was successfully dissolved and spun into regenerated lyocell fibres with mechanical properties superior to those of standard lyocell fibres [13]. Likewise, reactive dyes are covalently bonded to the cellulose polymer and need to be removed in a pretreatment stage.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, recycling is achieved by drawing fabrics into yarns and fibers, and then, reassembling them into recyclable yarns for the production of textiles and other materials, such as nonwovens, carpet liners [5], sound insulation materials, thermal insulation materials [6], deodorizing materials, and filtering materials; thus, converting waste garments into recyclable ones [7].…”
Section: Introductionmentioning
confidence: 99%
“…Both Saxcell 7 and Haule et al [10][11][12] have taken another step by utilizing their cotton waste pulps to make fibers. Saxcell claim to have succeeded both by the viscose and lyocell processes, 7 whereas Haule et al [10][11][12] utilized the lyocell process. In a recent press release, Lenzing 13 announced the launch of Refibra TM , a version of TENCEL Õ fiber made out of cotton scrap and wood pulp.…”
mentioning
confidence: 99%